Influence of counterbody material on sliding wear behaviour of NiCrSiB-TiB2 plasma sprayed material - Стороженко, M.С.; Уманский, А.П.; Терентьев, А.Е.; Костенко, А.Д. (Problems of Tribology, 2016)
Wear behavior of NiCrSiB-20wt.%TiB2 plasma sprayed coatings against NiCrSiB, Al2O3 and Cr2O3 counter bodies is studied under dry sliding conditions at sliding speed of 0.5 m/s and at constant load applied to the pin of 0.8 N. Running against the NiCrSiB plasma-sprayed NiCrSiB-20wt.%TiB2 coating exhibits wear rate of 14 μm/km. The specific wear rate of NiCrSiB-20wt.%TiB2 coatings against Cr2O3 is equal 12 μm/km and against Al2O3 is 10 μm/km. The investigation of worn surfaces shows that oxidative wear mechanism is proved to be dominant for friction couples. In all cases protective oxide layer is formed on the on the contact surfaces and protects the coating against any pronounced damages. Key words: nickel - based self-fluxing alloy, titanium diboride, plasma-sprayed coating, wear.